Answered

Welcome to Westonci.ca, the place where your questions find answers from a community of knowledgeable experts. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.

If f(x)=7-2x find f(3)+6

Sagot :

To get the answer we have to substitute x=3 and add 6 to the result.
Lets do this
f(x)=7-2x
f(3)=7-2*3=7-6=1
f(3)+6=1+6=7 - its the result
Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. We're glad you visited Westonci.ca. Return anytime for updated answers from our knowledgeable team.